The veil of circumstance technology, values, dehumanization and the future of economics and politics - Moller, Jorgen Ostrom (ISEAS - Yusof Ishak Institute, 2016)
Professor Jorgen Orstrom Moller is never one to evade the complexities and subtleties of current affairs. In this book he uses an interdisciplinary approach to discuss the intrinsic issues, including globalization, that are shaping the world.